Analisis Wacana Kritis Kajian Norman Fairclough dalam Wacana “Turbulensi Kurikulum Merdeka” Harian Kompas.com - Teti Sobari; Agus Abdurohim; Raden Ika Mustika; Sabila Idzni Suryana (Badan Pengembangan dan Pembinaan Bahasa, 2025)
The implementation of the independent curriculum at the time was a hot issue in education circles, and many ideas responded to the independent curriculum, both pro and con. This study aims to identify the challenges and obstacles in the implementation of the independent curriculum through a three-dimensional analysis: micro, medo, and macrostructure. This study uses a qualitative-descriptive method. The data collection technique was carried out through documentation of the news text entitled